COVID‐19 outcomes in children, adolescents and young adults with cancer. Issue 11 (19th July 2022) - Parker, Rebecca S.; Le, Justin; Doan, Andrew; Aguayo‐Hiraldo, Paibel; Pannaraj, Pia S.; Rushing, Teresa; Malvar, Jemily; O'Gorman, Maurice R.; Dien Bard, Jennifer; Parekh, Chintan
Abstract: Pediatric oncology patients are at risk for poor outcomes with respiratory viral infections. Outcome data for COVID‐19 in children and young adults with cancer are needed; data are sparse for obese/overweight and adolescent and young adult subgroups. We conducted a single center cohort study of COVID‐19 outcomes in patients younger than 25 years with cancer. Candidate hospitalization risk factors were analyzed via univariable and multivariable analyses. Eighty‐seven patients with cancer and COVID‐19 were identified. Most were Hispanic/Latinx (n = 63, 72%). Forty‐two (48%) were overweight/obese. Anticancer therapy included chemotherapy only (n = 64, 74%), chimeric antigen receptor T‐cells (CAR‐T, n = 7), hematopoietic stem cell transplantation (HSCT, n = 12), or CAR‐T and HSCT (n = 4). There was no COVID‐19 related mortality. Twenty‐six patients (30%) required COVID‐19 related hospitalization; 4 required multiple hospitalizations. Nine (10%) had severe/critical infection; 6 needed intensive care. COVID‐19 resulted in anticancer therapy delays in 22 (34%) of 64 patients on active therapy (median delay = 14 days). Factors associated with hospitalization included steroids within 2 weeks prior to infection, lymphopenia, previous significant non‐COVID infection, and low COVID‐19 PCR cycle threshold value. CAR‐T recipients with B‐cell aplasia tended to have severe/critical infection (3 of 7 patients). A COVID‐19 antibody response was detected in 14 of 32 patients (44%). A substantial proportion of COVID‐19 infected children and young adults with cancer require inpatient management; morbidity may be high in B‐cell immunodeficiency. However, a majority of patients can be taken through chemotherapy without prolonged therapy delays. Viral load is a potential outcome predictor in COVID‐19 in pediatric cancer. Abstract : What's new? It is important to understand outcomes of COVID‐19 in pediatric patients with cancer, not only to appropriately treat the COVID‐19, but also to know how best to modify cancer therapy. Highly immunosuppressive cancer therapy can add to the risk of severe infection, but stopping cancer treatment can allow the cancer to progress. Here, the authors undertook a single‐center cohort study of COVID‐19 outcomes in 87 patients under age 25 with cancer. None died of COVID‐19, but 30% required hospitalization. Risk factors included lymphopenia, recent steroids, CAR T‐cell therapy, and high viral load. Most patients could continue chemotherapy without prolonged delays.